Inhibitors of Bacterial Extracellular Vesicles - Chen, Jianwei; Zhang, Hongfang; Wang, Siqi; Du, Yujie; Wei, Bin; Wu, Qiang; Wang, Hong (Frontiers in Microbiology, 2022)
Both Gram-positive and Gram-negative bacteria can secrete extracellular vesicles (EVs), which contain numerous active substances. EVs mediate bacterial interactions with their hosts or other microbes. Bacterial EVs play a double-edged role in infections through various mechanisms, including the delivery of virulence factors, modulating immune responses, mediating antibiotic resistance, and inhibiting competitive microbes. The spread of antibiotic resistance continues to represent a difficult clinical challenge. Therefore, the investigation of novel therapeutics is a valuable research endeavor for targeting antibiotic-resistant bacterial infections. As a pathogenic substance of bacteria, bacterial EVs have gained increased attention. Thus, EV inhibitors are expected to function as novel antimicrobial agents. The inhibition of EV production, EV activity, and EV-stimulated inflammation are considered potential pathways. This review primarily introduces compounds that effectively inhibit bacterial EVs and evaluates the prospects of their application.